2011
DOI: 10.1007/s11033-011-1415-9
|View full text |Cite
|
Sign up to set email alerts
|

Induction of toll-like receptor (TLR) 2, and MyD88-dependent TLR- signaling in response to ligand stimulation and bacterial infections in the Indian major carp, mrigal (Cirrhinus mrigala)

Abstract: Toll-like receptor 2 (TLR2) is a member of TLR family. It recognizes a wide range of bacteria and their products, and is involved in inducing innate immune responses. In this article, we reported inductive expression of TLR2 and myeloid differentiation primary response gene 88 (MyD88)-dependent signaling in the Indian major carp, mrigal (Cirrhinus mrigala) which is highly commercially important fish species in the Indian subcontinent. Ontogeny analysis of TLR2, MyD88 and TRAF6 (TNF receptor associated factor 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(29 citation statements)
references
References 38 publications
2
26
0
Order By: Relevance
“…Interestingly, in the present study, muscle showed the maximum MDA5 transcript level as compared to other tissues. Similar findings have been reported for genes associated with TLR signalling pathways such as tumour necrosis factor receptor-associated factor 6 (TRAF6) in mrigal, Cirrhinus mrigala (Basu et al, 2012). However, the exact functional role of the high expression is not known.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Interestingly, in the present study, muscle showed the maximum MDA5 transcript level as compared to other tissues. Similar findings have been reported for genes associated with TLR signalling pathways such as tumour necrosis factor receptor-associated factor 6 (TRAF6) in mrigal, Cirrhinus mrigala (Basu et al, 2012). However, the exact functional role of the high expression is not known.…”
Section: Discussionsupporting
confidence: 74%
“…Similar to many immune-related genes, EsMDA5 also showed constitutive expression in all the tissues tested (Su et al, 2010;Ohtani et al, 2011;Basu et al, 2012;Rajendran et al, 2012). The mRNA expression was found to be highest in muscle followed by the spleen, head kidney and hindgut.…”
Section: Discussionmentioning
confidence: 77%
“…In contrast, no il-8 mRNA regulation was observed after A. hydrophila in this model leading the authors to suggest a bacteria specific response [35]. Furthermore in the same study an upregulation of il-8 mRNA expression was observed in other tissues including liver, kidney, intestine and blood [35,36]. Our results are compatible with those found in carp although the expression level of this transcript in internal organs of the eels infected with V. vulnificus should be addressed in future analyses.…”
Section: Discussionmentioning
confidence: 67%
“…The TLR2 is capable of recognizing a broad spectrum of microbes, partly due to its ability to form heterodimers with TLR1 and TLR6 [11]. It recognizes a wide range of bacteria and their products, and is involved in inducing innate immune responses [12]. Meanwhile, TLR3 play an important role in fish's defense against both viral and bacterial infection proved by the upper transcripts expression when challenged by poly:C and Vibrio parahemolyticus [13].…”
Section: Introductionmentioning
confidence: 99%